The Association of Mitochondrial tRNACys G5783A Mutation with Major Depressive Disorder in Two Han Chinese Families - Jing P; Yu H; Sun W; Liang M; Xia T; Yang H; Chen P; Li J; Zhang X (Neuropsychiatric Disease and Treatment)
Pan Jing,1,2 Haihang Yu,1,2 Wenxi Sun,3,4 Ming Liang,5 Tingting Xia,5 Haidong Yang,6 Peng Chen,3,4 Jin Li,3,4 Xiaobin Zhang3,4 1Department of Psychiatry, Affiliated Kangning Hospital of Ningbo University, Ningbo, People’s Republic of China; 2Department of psychiatry, Ningbo Kangning Hospital, Ningbo, People’s Republic of China; 3Department of Psychiatry, Suzhou Guangji Hospital, Suzhou, People’s Republic of China; 4Department of Psychiatry, Affiliated Guangji Hospital of Soochow University, Suzhou, People’s Republic of China; 5Department of Psychiatry, Xiangshan Third People’s Hospital, Ningbo, People’s Republic of China; 6Department of Psychiatry, Lianyungang Fourth People’s Hospital, Lianyungang, People’s Republic of ChinaCorrespondence: Xiaobin Zhang, Department of Psychiatric, Suzhou Guangji Hospital, 11 Guangqian Road, Suzhou, Jiangsu, 215003, People’s Republic of China, Email zhangxiaobim@163.comObjective: In this study, we examined the genetic, medical, and molecular traits of two Han Chinese families with the tRNACys G5783A mutation to investigate the relationship between mitochondrial DNA (mtDNA) mutations and major depressive disorder (MDD).Methods: Clinical data and comprehensive mitochondrial genomes were collected from the two families. Variants were assessed for evolutionary conservation, allelic frequencies, and their structural and functional impacts. The study involved detailed mitochondrial whole genome analysis, as well as phylogenetic and haplotype analyses of the probands and other family members.Results: We detailed the genetic, clinical, and molecular profiles of two Han Chinese families with MDD. These families exhibited a range of depression severities and notably low penetrance of MDD. Analysis of the mitochondrial genomes revealed a homoplasmic tRNACys G5783A mutation. This mutation was found at a highly conserved cytosine at position 50 (C50) in the TΨC stem of tRNACys, with a conserved coefficient of 100% across 17 species. Additionally, distinctive mtDNA polymorphisms associated with haplogroups H2 were identified.Conclusion: The identification of the tRNACys G5783A mutation in two unrelated individuals with depression strongly suggests that this mutation may play a role in the development of major depressive disorder (MDD). These Chinese families revealed low penetrances of MDD. Thus, the phenotypic tRNACys G5783A mutation expression associated with MDD may be impacted by nuclear modifier gene(s) or environmental factors.Keywords: major depressive disorder, mitochondrial DNA, tRNA, mutation, haplogroup, Chinese